Alice Lakwena & the holy spirits: war in Northern Uganda, 1985-97 - Behrend, Heike (Eastern African studies, 1999)
In August 1986, Alice Auma, a young Acholi woman in northern Uganda, proclaiming herself under the orders of a Christian spirit, raised an army called the 'Holy Spirit Mobile Forces' and with it waged a war, not only against the National Resistance Army of the government but also against internal enemies in the form of 'impure' soldiers, witches and sorcerers. She came close to her goal of overthrowing the government but was defeated and fled to Kenya. This book gives an account of the movement from within, based on interviews with and writings of its members, and concludes with an account of the successor movements into which Alice's forces fragmented, including the 'Lord's Resistance Army', actively involved in the civil wars of the Sudan and Uganda. North America: Ohio U Press; Uganda: Fountain Publishers